Deep Learning dalam Kurikulum Merdeka Berdasarkan Kebijakan Kementerian Pendidikan Dasar dan Menengah Republik Indonesia di Sekolah Dasar - Mujtahid; Ali Hasan Assidiqi; Dini Sadiyah (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This study aims to analyze the implementation of Deep Learning in the Independent Curriculum, based on the policies of the Ministry of Primary and Secondary Education of the Republic of Indonesia, at the elementary school level. The background of this research is based on the importance of transforming national education in facing technological developments and the demands of 21st-century competencies that emphasize critical, creative, collaborative, and communicative thinking skills. The Deep Learning approach is presented as an effort to create more meaningful, contextual, and student-centered learning so that students not only understand the material theoretically but also are able to apply it in their daily lives. This study used a qualitative approach with library research. Data were obtained through a documentary study of various sources, such as government regulations, official documents of the Ministry of Primary and Secondary Education of the Republic of Indonesia, books, scientific journals, and previous research results relevant to the research topic. Data analysis was conducted using descriptive qualitative techniques through the stages of data reduction, data presentation, and conclusion drawing. Research results indicate that the implementation of Deep Learning within the Independent Curriculum in elementary schools is carried out through project-based learning, problem-based learning, collaborative learning, the use of technology, and reflection activities. This approach has a positive impact on increasing student engagement, higher-order thinking skills (HOTS), creativity, communication skills, and character development in line with the Pancasila Student Profile. However, the implementation of Deep Learning still faces various obstacles, such as limited teacher understanding, the use of conventional learning methods, and limited learning facilities and infrastructure in some elementary schools. Therefore, improving teacher competency, supporting learning facilities, and ongoing mentoring are needed to ensure the optimal and equitable implementation of Deep Learning within the Independent Curriculum across all elementary schools in Indonesia. Keywords: Deep Learning, Independent Curriculum, Education Policy, Elementary Schools, Deep Learning. Abstrak Penelitian ini bertujuan untuk menganalisis implementasi Deep Learning dalam Kurikulum Merdeka berdasarkan kebijakan Kementerian Pendidikan Dasar dan Menengah Republik Indonesia pada jenjang sekolah dasar. Latar belakang penelitian ini didasarkan pada pentingnya transformasi pendidikan nasional dalam menghadapi perkembangan teknologi dan tuntutan kompetensi abad ke-21 yang menekankan kemampuan berpikir kritis, kreatif, kolaboratif, dan komunikatif. Pendekatan Deep Learning hadir sebagai upaya untuk menciptakan pembelajaran yang lebih bermakna, kontekstual, dan berpusat pada peserta didik sehingga peserta didik tidak hanya memahami materi secara teoritis, tetapi juga mampu mengaplikasikannya dalam kehidupan sehari-hari. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian kepustakaan (library research). Data diperoleh melalui studi dokumentasi terhadap berbagai sumber, seperti peraturan pemerintah, dokumen resmi Kementerian Pendidikan Dasar dan Menengah Republik Indonesia, buku, jurnal ilmiah, serta hasil penelitian terdahulu yang relevan dengan topik penelitian. Teknik analisis data dilakukan secara deskriptif kualitatif melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa implementasi Deep Learning dalam Kurikulum Merdeka di sekolah dasar dilakukan melalui pembelajaran berbasis proyek (project based learning), pembelajaran berbasis masalah (problem based learning), pembelajaran kolaboratif, pemanfaatan teknologi, dan kegiatan refleksi pembelajaran. Pendekatan tersebut memberikan dampak positif terhadap peningkatan keaktifan peserta didik, kemampuan berpikir tingkat tinggi (higher order thinking skills/HOTS), kreativitas, kemampuan komunikasi, serta pembentukan karakter sesuai Profil Pelajar Pancasila. Namun demikian, implementasi Deep Learning masih menghadapi berbagai kendala, seperti keterbatasan pemahaman guru, penggunaan metode pembelajaran konvensional, serta keterbatasan sarana dan prasarana pembelajaran di beberapa sekolah dasar. Oleh karena itu, diperlukan peningkatan kompetensi guru, dukungan fasilitas pembelajaran, dan pendampingan berkelanjutan agar implementasi Deep Learning dalam Kurikulum Merdeka dapat berjalan secara optimal dan merata di seluruh sekolah dasar di Indonesia. Kata Kunci: Deep Learning, Kurikulum Merdeka, Kebijakan Pendidikan, Sekolah Dasar, Pembelajaran Mendalam.